2020
DOI: 10.1002/ijc.32854
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian cancer‐associated mesothelial cells induce acquired platinum‐resistance in peritoneal metastasis via the FN1/Akt signaling pathway

Abstract: Peritoneal dissemination of ovarian cancer (OvCa) arises from the surface of the peritoneum, covered by monolayer of mesothelial cells (MCs). Given that both OvCa cells and MCs are present in the same peritoneal metastatic microenvironment, they may establish cell‐to‐cell crosstalk or phenotypic alterations including the acquisition of platinum‐resistance in OvCa cells. Herein, we report how OvCa‐associated mesothelial cells (OCAMs) induce platinum‐resistance in OvCa cells through direct cell‐to‐cell crosstalk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
61
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(66 citation statements)
references
References 53 publications
5
61
0
Order By: Relevance
“…FN1 has been shown to promote metastasis in various types of tumors. [ 39 41 ] Recently, Li et al [ 42 ] reported that FN1 promotes cutaneous melanoma proliferation and metastasis by inhibiting apoptosis and regulating epithelial-to-mesenchymal transition, which is consistent with our results. APOA1 is the main protein constituent of high-density lipoprotein, which shuttles excess cholesterol from organs to the liver for excretion.…”
Section: Discussionsupporting
confidence: 92%
“…FN1 has been shown to promote metastasis in various types of tumors. [ 39 41 ] Recently, Li et al [ 42 ] reported that FN1 promotes cutaneous melanoma proliferation and metastasis by inhibiting apoptosis and regulating epithelial-to-mesenchymal transition, which is consistent with our results. APOA1 is the main protein constituent of high-density lipoprotein, which shuttles excess cholesterol from organs to the liver for excretion.…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, reports have indicated that these cancer-associated MCs promote OvCa progression via various cell-to-cell crosstalk with OvCa cells [ 9 , 16 , 51 ]. In this context, we comprehensively defined the MCs altered by OvCa as OCAMs and demonstrated their features [ 9 , 15 , 16 , 17 , 19 ]. Based on Dr. Stephen Paget’s theory, seeds of OvCa cells cultivate the soil of MCs for OCAMs of the peritoneum by nourishing them with TGF-β1, which promotes the progression of peritoneal dissemination.…”
Section: Biological Process Of Peritoneal Dissemination Of Ovcamentioning
confidence: 99%
“…The changes in OCAMs are mainly due to mesenchymal transition but may also be viewed as transdifferentiation. While there are no unique markers for OCAM, it has been reported that the expression of genes encoding proteins that are known markers of epithelial–mesenchymal transition (EMT), such as E-cadherin decrease and N-cadherin increase, is altered in MCs induced by TGF-β1 [ 9 ]. We speculate that as cancer cells become more malignant as they become more undifferentiated, they may become more closely related to each other as they transdifferentiate.…”
Section: Ocams Affect Ovca Adhesion On the Peritoneummentioning
confidence: 99%
See 2 more Smart Citations